Estrogen’s bone-protective effects may involve differential IL-1 receptor regulation in human osteoclast-like cells - Sunyer, Teresa (American Society for Clinical Investigation, 1999)
Declining estrogen levels during the first postmenopausal decade lead to rapid bone loss and increased fracture risk that can be reversed by estrogen replacement therapy. The bone-protective effects of estrogen may involve suppression of inflammatory cytokines that promote osteoclastogenesis and bone resorption, such as IL-1, TNF-α, and IL-6. We investigated whether estrogen modulates IL-1 actions on human osteoclasts (OCs) and other bone cell types. Isolated human OCs and primary bone marrow–derived OC-like cells expressed both the signaling (IL-1RI) and decoy (IL-1RII) IL-1 receptors, whereas only IL-1RI was detected in osteoblasts. IL-1RII/IL-1RI mRNA ratios and release of soluble IL-1RII (sIL-1RII) were lower in OC-like cells derived from women in the late postmenopausal period compared with younger women, but were unrelated to male donor age, suggesting that estrogen might play a role in regulating IL-1 receptor levels in vivo. Estrogen directly reduced in vitro OC-like cell IL-1RI mRNA levels while increasing IL-1RII mRNA levels and sIL-1RII release. These estrogenic events were associated with inhibited IL-1–mediated cytokine (IL-8) mRNA induction and cell survival, i.e., increased apoptosis. In contrast, estrogen did not alter IL-1R levels or IL-1 responsiveness in primary human osteoblasts or bone marrow stromal cells. We conclude that one novel mechanism by which estrogen exerts bone-protective effects may include a selective modulation of IL-1R isoform levels in OC or OC-like cells, thereby reducing their IL-1 responsiveness and cell survival. Conversely, this restraint on IL-1 actions may be lost as estrogen levels decline in aging women, contributing to an enhanced OC-mediated postmenopausal bone loss.